Scattering of Elastic Waves by an Inhomogeneous Boundary in the Acoustic Testing of Permanent Joints - A. R. Baev; N. V. Levkovich; A. L. Mayorov; M. V. Asadchaya (Приборы и методы измерений)
Improving the reliability and testing performance of permanent joints оf different materials made by welding, spraying, gluing, soldering and other methods is an important production task, for which the ultrasonic method is the simplest and most effective. The purpose of this work was to expand the technical possibilities and increase the sensitivity of ultrasonic testing of adhesion defects of materials joints based on the establishment of laws governing the formation of a scattering field of elastic waves from an inhomogeneous boundary in three-dimensional space and issuing recommendations for the development of suggested method.For the first time, in the framework of classical concepts, the scattering fields of elastic waves of an acoustic beam with a circular cross section moving across the boundary of a semi-infinite defect are calculated. It is proposed to use a phase shift between the waves reflected from the indicated surfaces, which varies in the range of π/4–π, as an important parameter of the material joint's defect. It has a significant effect on the field pattern and its angular amplitude extrema — minima and maxima of different orders when the defect boundary is moved relative to the center of the acoustic beam spot.The features of the evolution of the structure of the scattering field are established, which make it possible to identify optimal conditions for the detection of weakly reflective defects in sound. It is shown that it is possible in principle to estimate the defect's area by measuring a change in the amplitude of the primary maximum of the radiation pattern of the scattered waves.Specific examples show the effectiveness of using the proposed method for a number of practical applications.